Molecular Mechanisms for Microbe Recognition and Defense by the Red Seaweed Laurencia dendroidea - Louisi Souza de Oliveira (American Society for Microbiology, 2017)
ABSTRACT The ability to recognize and respond to the presence of microbes is an essential strategy for seaweeds to survive in the marine environment, but understanding of molecular seaweed-microbe interactions is limited. Laurencia dendroidea clones were inoculated with the marine bacterium Vibrio madracius. The seaweed RNA was sequenced, providing an unprecedentedly high coverage of the transcriptome of Laurencia, and the gene expression levels were compared between control and inoculated samples after 24, 48, and 72 h. Transcriptomic changes in L. dendroidea in the presence of V. madracius include the upregulation of genes that participate in signaling pathways described here for the first time as a response of seaweeds to microbes. Genes coding for defense-related transcription activators, reactive oxygen species metabolism, terpene biosynthesis, and energy conversion pathways were upregulated in inoculated samples of L. dendroidea, indicating an integrated defensive system in seaweeds. This report contributes significantly to the current knowledge about the molecular mechanisms involved in the highly dynamic seaweed-bacterium interactions. IMPORTANCE Marine bacteria are part of the healthy microbiota associated with seaweeds, but some species, such as Vibrio spp., are frequently associated with disease outbreaks, especially in economically valuable cultures. In this context, the ability of seaweeds to recognize microbes and, when necessary, activate defense mechanisms is essential for their survival. However, studies dedicated to understanding the molecular components of the immune response in seaweeds are rare and restricted to indirect stimulus. This work provides an unprecedentedly large-scale evaluation of the transcriptional changes involved in microbe recognition, cellular signaling, and defense in the red seaweed Laurencia dendroidea in response to the marine bacterium Vibrio madracius. By expanding knowledge about seaweed-bacterium interactions and about the integrated defensive system in seaweeds, this work offers the basis for the development of tools to increase the resistance of cultured seaweeds to bacterial infections.